ACTIVITY TEST AND REGENERATION OF NiMo/Z CATALYST FOR HYDROCRACKING OF WASTE PLASTIC FRACTION TO GASOLINE FRACTION - Rodiansono Rodiansono; Wega Trisunaryanti (Indonesian Journal of Chemistry, 2005)
Activity test and regeneration of NiMo/active natural zeolite catalyst for hydrocracking of waste plastic fraction of polyprophylene (PP) type have been carried out. The catalysts was prepared by loading Mo followed by Ni Metals onto the natural zeolite (Z) sample, then calcined at 500oC, oxidized and reduced at 400oC under nitrogen, oxygen and hydrogen stream, respectively. The characterization of catalysts including spesific surface area, average pore radius, and total pore volume were performed by gas sorption analyzer, amount of total acid sites was determined by gas sorption method, and acid site strength was confirmed by IR spectroscopy. The hydrocracking process was carried out in a semi-flow reactor system at 360 oC and catalyst:feed ratio 0.5 under hydrogen stream (150 mL/hour). The feed was vaporized from the pyrolisis reactor into the hydrocracking reactor. A liquid product was collected and analyzed by gas chromatography (GC) and gas chromatography-mass spectroscopy (GC-MS). The characterization results showed that spesific surface area, average pore radius, and total pore volume of the Z sample decreased after loading of the Ni and Mo metals. Amount of total acid sites of the NiMo/Z catalyst was higher than that of the Z sample. The activity of NiMo/Z catalyst decreased after several continously runs. Its regeneration produced the NiMo/Z reg catalyst with similar activity and selectivity to the fresh catalyst (NiMo/Z). The activity of catalysts at the optimum condition followed the order of NiMo/Z reg>NiMo/Z>Z (conversion of hydrocarbon C>12) and NiMo/Z reg>NiMo/Z>Z (total yield of gasoline fraction). The selectivity of catalysts for C7-C8 product followed the order of Z>NiMo/Z>NiMo/Z reg.